Seed traits and bird species influence the dispersal parameters of wetland plants. (12th May 2016) - Reynolds, Chevonne; Cumming, Graeme S.
Summary: Patterns of seed dispersal are strongly influenced by disperser and propagule traits. However, the relative importance of these characteristics for dispersal outcomes is unclear. We investigated differences in the potential dispersal of wetland plants between Egyptian goose ( Alopochen aegyptiaca ) and red‐billed teal (Anas erythrorhyncha ), two southern African Anatidae. The seeds of seven wetland plants with varying traits were fed to the birds and the dispersal parameters of gut passage time, recoverability and germinability of ingested seed were determined. We tested the effect of disperser species and seed traits on dispersal parameters. In addition, we determined whether increased retention times lead to lower recovery and germination of ingested seed. We predicted that the seed traits of small size and increased hardness would be better at mediating the trade‐off between retention time and recoverability and germination, but that this might differ between vectors. The dispersal parameters varied significantly between Egyptian goose and red‐billed teal. In particular, Egyptian goose had longer average and maximum retention times of seeds, but also higher recoverability. Furthermore, short seeds had significantly longer average retention time and were also recovered in the highest numbers. Short seed length potentially facilitates endozoochory by two complementary mechanisms. First, short seeds are less digestible, leading to higher recoverability. Second, due to lower digestibility, short seeds are able to survive at longer retention times to be dispersed further, similarly to hard seeds (with hardness positively correlated with seed mass). Our results suggest that small seed length and hardness are optimal seed traits facilitating endozoochory in wetland plants. Dispersal parameters were also influenced by the bird species and indicate that differences in vector morphology and digestive physiology may likely have important consequences for seed dispersal. Hence, vector characteristics should be given more explicit consideration in future studies of seed dispersal in aquatic systems.